Spatial and Temporal Interactions between Shape Representations in Human Vision - Slugocki, Michael (My University, 2019)
The human visual system has the remarkable capacity to transform spatio-temporal patterns of light into structured units of perception. Much research has focused on how the visual system integrates information around the perimeter of closed contours to form the perception of shape. This dissertation extends previous work by investigating how the perception of curvature along closed-contour shapes is affected by the presence of additional shapes that appear close to the target shape in space and/or time. Chapter 2 examined the ability of shape mechanisms at representing low frequency curvature in the presence of a higher frequency component along contours in multi-shape displays. We found that additions of high amplitude, high frequency curvature along a contour path can modulate the strength of interaction observed between shapes, and thus attenuates the contribution of low frequency components in interactions between neighbouring contours. Chapter 3 examined what curvature features are of importance in modulating phase dependent interactions between shapes. Results revealed that phase-dependent masking does not depend on curvature frequency, but is related to sensitivity for phase shifts in isolated contours, and is affected by both positive and negative curvature extrema. Computational simulations aimed at modelling the population responses evoked in intermediate shape processing areas (i.e., V4) suggest sensitivity to shifts in phase of shapes is not well captured by such a population code, and therefore alternative explanations are required. Chapter 4 examined how sensitivity to curvature deformations along the contour of a closed shape changes as a function of polar angle, angular frequency, and spatial uncertainty. Results show that human observers are, at first approximation, uniformly sensitivity to curvature deformations across all polar angles tested, and this result holds despite changes in angular frequency and spatial uncertainty. Chapter 5 examined whether the strength of spatial masking between shapes is affected by the presentation of a temporal mask. Our results demonstrate that a temporal mask affected spatial masking only when it preceded the target-mask stimulus by 130-180ms. Furthermore, the effects of a temporal mask on spatial masking are approximately additive, suggesting that separate components contribute to spatial and temporal interactions between shapes.
Keywords: Shape perception; Psychophysics; Radial frequency contours; Human vision; Lateral masking